Analisis Sumber Dan Penggunaan Modal Kerja Dalam Meningkatkan Likuiditas Pada Usaha Furniture Sunny Meubel Di Kota Metro - Annisa, Ulin; Sugeng, Sugeng (Universitas Muhammadiyah Metro, 2022)
Ulin Anisa. 2021. Analysis of sources and use of working capital in increasing liquidity in the Sunny Furniture business in Metro City. Thesis, Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro. Advisor I Dr. Afdal Mazni, S.E., M.M. Advisor II Karnila Ali, B.BUS., M.P.A. Sources of working capital are production support tools that are used to support and produce goods and services. This study aims to determine the size of capital resources and the use of working capital, determine the level of company liquidity and find out how capital resources and use of capital in increasing the liquidity of Sunny Furniture Furniture business. The research method used is a descriptive approach, namely research that seeks to collect and present company data in a ready-made form derived from financial statements in the form of balance sheets and income statements while some data comes from direct sources through questions and answers. The analytical tools used are analysis of reports on changes in capital, analysis of reports on sources and use of working capital and analysis of liquidity ratios measured by the current ratio, quick ratio, and net working capital. The results of the research on the management of sources and the use of the company's working capital for a period of 5 years have been good. The results of the liquidity ratio are good, because as a general guideline the ratio level of 2.00 can be considered good. Keywords: Working capital, liquidity, current ratio, quick ratio, and net working capital.